2019
DOI: 10.1016/j.enconman.2019.01.029
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on energy and exergy performances of a microencapsulated phase change material slurry based photovoltaic/thermal module

Abstract: Link to publication on Research at Birmingham portal General rights Unless a licence is specified above, all rights (including copyright and moral rights) in this document are retained by the authors and/or the copyright holders. The express permission of the copyright holder must be obtained for any use of this material other than for purposes permitted by law. • Users may freely distribute the URL that is used to identify this publication. • Users may download and/or print one copy of the publication from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…For the heat-absorbing plate covered by photovoltaic panels, there are radiation and convection to the ambient. Hence, the net heat flow obtained by the heat-absorbing plate qcover can be calculated as [13]:…”
Section: Governing Equation and Boundary Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…For the heat-absorbing plate covered by photovoltaic panels, there are radiation and convection to the ambient. Hence, the net heat flow obtained by the heat-absorbing plate qcover can be calculated as [13]:…”
Section: Governing Equation and Boundary Conditionsmentioning
confidence: 99%
“…Much research has been conducted to investigate the performance of different types of nanofluids in enhancing the performance of photovoltaic thermal system e.g., non-metal/metal oxide nanofluid, metal elemental nanofluid [5][6][7][8], and inorganic carbon-based nanofluid [6,7,[9][10][11][12]. In addition, some researches have been conducted to optimize the heat exchanger structure on the back of the photovoltaic panel in using nanofluid/phase change material/ microcapsule phase change nanofluid, in order to improve the efficiency of the PVT system [3,4,[13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Exergy and entropy are the two important concepts in the thermodynamical systems, the former shows the system's ability to execute useful work whilst the latter indicates the system's inability to execute useful work [33]. The important concept of exergy is used in nanofluid-based PVT system also by various researchers [34][35][36][37][38]. Sardarabadi et al [34] experimentally investigated the performance of nanofluid SiC/water nanofluid in PVT system.…”
Section: Introductionmentioning
confidence: 99%
“…For this purpose, they used a combination of nanofluid (ZnO/water) and PCM (paraffin wax), which resulted in an attainment of 13.6% of overall exergy efficiency. With a similar objective of improving the exergy performance, a microencapsulated PCM slurry was used as a cooling fluid by Yu et al [37]. In their study, the exergy performance was mapped with the variation of the melting point and slurry concentration.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the thermal and exergy efficiencies have been improved 8.3% and 3.23%, respectively. 81 Other researchers have used MPCM to improve cooling performance of different systems. 82,83 In recent years, with the advancement of technology and the production of materials in nano scales, nanomaterials are widely used in various fields including drug delivery, 84,85 adsorption, 86 heat transfer and natural convection, 87 and desalination membranes.…”
Section: Introductionmentioning
confidence: 99%